2017
DOI: 10.1103/physrevphyseducres.13.010102
|View full text |Cite
|
Sign up to set email alerts
|

Electronics lab instructors’ approaches to troubleshooting instruction

Abstract: In this exploratory qualitative study, we describe instructors' self-reported practices for teaching and assessing students' ability to troubleshoot in electronics lab courses. We collected audio data from interviews with 20 electronics instructors from 18 institutions that varied by size, selectivity, and other factors. In addition to describing participants' instructional practices, we characterize their perceptions about the role of troubleshooting in electronics, the importance of the ability to troublesho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 45 publications
(65 reference statements)
2
30
0
Order By: Relevance
“…This kind of longitudinal study has not been conducted previously in part because there are significant theoretical and practical barriers to such a study. For example, there are many possible learning goals for physics lab courses, including reinforcing students' understanding of physics concepts [2,7,8]; teaching students' practical lab skills such as troubleshooting, critical thinking, and measurement skills [4,5,9,10]; and fostering students' understanding of, and appreciation for, the nature and importance of experimental physics [5,7,8,11]. Longitudinal investigations of improvement in students' conceptual knowledge over multiple lab courses would be difficult given that the majority of lab courses at different levels (e.g., introductory to advanced) target a wide range of physics topics with only small overlap in the particular physics concepts used.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of longitudinal study has not been conducted previously in part because there are significant theoretical and practical barriers to such a study. For example, there are many possible learning goals for physics lab courses, including reinforcing students' understanding of physics concepts [2,7,8]; teaching students' practical lab skills such as troubleshooting, critical thinking, and measurement skills [4,5,9,10]; and fostering students' understanding of, and appreciation for, the nature and importance of experimental physics [5,7,8,11]. Longitudinal investigations of improvement in students' conceptual knowledge over multiple lab courses would be difficult given that the majority of lab courses at different levels (e.g., introductory to advanced) target a wide range of physics topics with only small overlap in the particular physics concepts used.…”
Section: Introductionmentioning
confidence: 99%
“…Most instructors described instances of students enacting revisions as part of the troubleshooting process [9]. We have previously shown that instructors think troubleshooting is extremely important [36] and that a major goal of electronics is for students to build circuits that work [37]. In addition, instructors believe that since "nothing works the first time" [38] troubleshooting and revisions are a required part of working with electronics.…”
Section: Discussionmentioning
confidence: 99%
“…Emotions that might, on their face, seem negative, can ultimately lead to positive outcomes. For instance, "student frustration and struggle" are "necessary features of learning environments that promote ownership" (Dounas-Frazer & Lewandowski, 2017…”
Section: Emotionmentioning
confidence: 99%
“…For instance, in parallel to studies on identity, one could take a lens of examining classroom activity structures that may make some responses to challenge more or less available to students in certain moments (Shah, 2013;Carlone et al, 2014;Hand & Gresalfi, 2015). Given physics education research demonstrating that many physics faculty express ideas around physics ability as innate (Zwickl et al, 2014;Dounas-Frazer & Lewandowski, 2017;Scherr et al, 2017), examining the classroom and departmental environments that faculty set up should be a focus of study. For instance, Johnson et al (2017) have suggested that faculty messaging that aligns with growth mindset is one aspect of a departmental culture that is supportive of women of color.…”
Section: Limitationsmentioning
confidence: 99%